Sex difference in development of diabetes and cardiovascular disease on the way from obesity and metabolic syndrome - Prospective study of a cohort with normal glucose metabolism - Onat, A; Hergenç, G; Keles, I; Dogan, Y; Türkmen, S; Sansoy, V (W B SAUNDERS CO-ELSEVIER INC, 2005)
Aim: The objective of this study was to investigate sex-specific differences existing on the way from (abdominal) obesity and metabolic syndrome (MS) to type 2 diabetes mellitus (DM) and cardiovascular disease (CVD), Methods: A population sample of 1974 men and women, representative of Turkish adults (mean age, 49 years), with normal glucose metabolism (GM) and free of CVD at baseline. was prospectively evaluated at a mean 4.1 years of follow-up. The term abnormal GM designated both DM and impaired fasting glucose (IFG). Metabolic syndrome was identified in 29% of men and 40% of women by the criteria of the National Cholesterol Education Program guidelines, Fatal and nonfatal CVD, diagnosed by clinical findings and Minnesota coding of resting electrocardiograms, developed in 121 subjects. Results: The cohort was dichotomized by the presence or absence of MS and of obesity defined by a body mass index of 30 kg/m(2) or greater, Compared with the major female group with no obesity or MS, women with MS, regardless of the presence of obesity, predicted highly significantly the development of abnormal GM with relative risks exceeding 2, whereas no independent significant association was noted in men with MS. Similar divergence of sexes pertained to the prediction of diabetes. When age, smoking status, grade of physical activity, IFG, DM, and the 4 groups with obesity and MS were analyzed for the prediction of CVD by logistic regression, men with MS. regardless of the presence of obesity, predicted highly significantly CVD (with relative risks ranging from 2 to 4), but neither DM nor IFG contributed independently. Conversely, in women, abnormal GM predicted CVD independent of age, smoking Status, and grade of physical activity, but the groups with obesity and MS failed to significantly contribute independently. Conclusions: In populations with prevalent MS, whereas women with normal GM are prone to DM within the context of MS and are exposed to CVD risk primarily by way of DM, men are prone to visceral adiposity, less susceptible to DM, and run CVD risk primarily by the intermediary of MS, largely independent of the DM component. (c) 2005 Elsevier Inc. All rights reserved.
Keywords: C-REACTIVE PROTEIN; CORONARY-HEART-DISEASE; GENDER-DIFFERENCE; RISK; PREVALENCE; MELLITUS; PARTICIPANTS; DEFINITION; DIAGNOSIS; ADULTS; Endocrinology & Metabolism